To do, not to do, or do something different : self-control and incarcerated youth offenders. - Khairiyah Kassim. (2009)
Incarcerated youth offenders (N = 25) were compared with non-offending youths (N = 25) in the aspect of self-control with the Stroop test and the Arithmetic switching task. Compared to the non-offenders, incarcerated youth offenders appeared to have larger switch costs in the switching task though they performed the same on the Stroop task. This suggests that incarcerated youth offenders may be able to stop themselves from an inappropriate behavior but they have difficulties in switching to an appropriate behavior, compared to non-offending youths.